A nationwide assessment of microplastic abundance in agricultural soils: The influence of plastic crop covers within the United Kingdom - Samuel J. Cusworth; William J. Davies; Martin R. McAinsh; Carly J. Stevens (Plants, People, Planet, 2024)
Societal Impact Statement Agricultural soils are substantial receptors of plastic pollution. Plastic crop covers, a facet of agriplastics, may represent an important contribution to microplastic load in agricultural soils. The authors present a nationwide study of agricultural soils in the United Kingdom, comparing microplastic load between sites where plastic crop covers are and are not used for carrot and potato production. Sites where plastic crop covers were used received a higher microplastic load compared with sites where no plastic crop cover was used. The effects of microplastic pollution are largely unknown, requiring further research to determine the impact on soil, crop and human health. Summary Agricultural soils are substantial receptors of plastic pollution, with agriplastics potentially making an important contribution to the overall microplastic load to agricultural soils. The intensive use and mismanagement of plastic crop covers, particularly plastic mulch films, nets and fleeces, represent a pollution pathway. In this study, we have analysed the microplastic concentrations in agricultural soils in 324 samples from 108 sites across the United Kingdom, where carrots or potatoes were grown, using a combined digestion and density separation method. Microplastics were stained with Nile Red and quantified using fluorescence microscopy. Microplastic concentrations ranged from 1320 to 8190 particles kg−1, with a mean of 3680 ± 129.1 particles kg−1. Where no plastic crop covers were used for potato and carrot production, a mean of 2667 ± 84.1 particles kg−1 were detected. At sites where plastic crop covers were used in the past 10 years, a mean of 4689 ± 147.1 particles kg−1 were recorded. There was a significant difference in microplastic abundance between sites where plastic crop covers were and were not used (p ≤ 0.001), confirming that plastic crop covers are an important source of microplastics to agricultural soils. Further studies are needed to investigate microplastic occurrence in the environment to better understand their impact on soil, crops and human health.